Paediatric Diabetes Insipidus: A Review (Dhaka Shishu (Children) Hospital Journal, 2022)
Diabetes insipidus is a disease characterized by partial or total inability to concentrate urine due to a vasopressin secretion deficiency (central diabetes insipidus), a resistance to its action (nephrogenic diabetes insipidus) or an excessive consumption of water (primary polydipsia). The main signs and symptoms of the disease are polydipsia, polyuria, and nocturia; central diabetes insipidus has an insidious onset, whereas nephrogenic diabetes insipidus has a gradual onset. Because of the advances in clinical, laboratory, imaging techniques and molecular biology, the etiologic diagnosis of diabetes insipidus has improved, from 50% of patients with idiopathic diabetes insipidus to 10%-20% of patients; therefore, it has been achieved more timely treatments, resulting in reduction of the risk of sequelae. Accordingly, it is pivotal to rule out secondary causes of diabetes insipidus, such as drug consumption or metabolic disorders in patients with nephrogenic diabetes insipidus, brain tumors, encephalic trauma, infiltrative diseases, autoimmune disorders or central nervous system infections in case of patients suffering from central diabetes insipidus. Regarding treatment, it is recommended the use of desmopressin, an analogue of vasopressin, for the treatment of central diabetes insipidus, whereas water consumption, decrease of salt consumption and treatment with diuretic and non-steroidal anti inflammatory drugs are recommended for treatment of patients with nephrogenic diabetes insipidus.DS (Child) H J 2021; 37(1): 64-70